Polytetrafluoroethylene for binders for electrochemical devices, binders for electrochemical devices, electrode mixtures, electrodes, and secondary batteries

A PTFE binder with specific molecular weight and properties forms an electrode mixture sheet with enhanced strength and stability, addressing the need for improved energy density in secondary batteries by eliminating the use of organic solvents and enhancing binding strength.

JP7667211B2Active Publication Date: 2025-04-22DAIKIN INDUSTRIES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023131153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-08-10
Publication Date
2025-04-22
Estimated Expiration
2043-08-10

AI Technical Summary

Technical Problem

Existing secondary batteries, such as lithium-ion batteries, require improvements in energy density and battery characteristics, and current polytetrafluoroethylene (PTFE) binders do not effectively form electrode mixtures with sufficient strength and stability.

Method used

A PTFE binder with a specific number average molecular weight of 3.0×10^6, low water content (0.050 mass % or less), and controlled aspect ratio of primary particles, which can be stretchable and extruded at low pressure, is used to form an electrode mixture sheet with enhanced strength and stability, eliminating the need for organic solvents.

Benefits of technology

The PTFE binder enables the formation of an electrode mixture sheet with excellent strength, reduces process and cost associated with organic solvents, and improves binding strength with active materials, leading to higher energy density and improved battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667211000001
    Figure 0007667211000001
  • Figure 0007667211000002
    Figure 0007667211000002
  • Figure 0007667211000003
    Figure 0007667211000003
Patent Text Reader

Abstract

To provide polytetrafluoroethylene for a binder for an electrochemical device, a binder for an electrochemical device, an electrode mixture, an electrode, and a secondary battery, which enable formation of an electrode mixture sheet excellent in strength.SOLUTION: Polytetrafluoroethylene is used in a binder for an electrochemical device, wherein a number average molecular weight is 3.0×106 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to polytetrafluoroethylene for binders for electrochemical devices, binders for electrochemical devices, electrode mixtures, electrodes, and secondary batteries. [Background technology]

[0002] Secondary batteries such as lithium-ion secondary batteries are used in small, portable electric and electronic devices such as notebook computers, mobile phones, smartphones, tablet computers, and ultrabooks, due to their high voltage, high energy density, low self-discharge, low memory effect, and the ability to be made extremely lightweight, and are also being put into practical use as a wide range of power sources, including on-board power sources for driving automobiles and large stationary power sources. There is a demand for secondary batteries to have even higher energy density, and further improvements in their battery characteristics are required.

[0003] Patent Document 1 describes an energy storage device in which at least one of the cathode and the anode contains a polytetrafluoroethylene composite binder material.

[0004] Patent Documents 2 and 3 describe the use of an aqueous dispersion of polytetrafluoroethylene as a binder in batteries. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2017-517862 [Patent Document 2] JP 2004-31179 A [Patent Document 3] Japanese Patent Application Publication No. 11-343317 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present disclosure is to provide a polytetrafluoroethylene for binders for electrochemical devices that can form an electrode mixture sheet having excellent strength, a binder for electrochemical devices, an electrode mixture, an electrode, and a secondary battery. [Means for solving the problem]

[0007] The present disclosure (1) relates to polytetrafluoroethylene used as a binder for electrochemical devices, the number average molecular weight of which is 3.0×10 6 The polytetrafluoroethylene is as above.

[0008] The present disclosure (2) relates to a binder for electrochemical devices consisting essentially of polytetrafluoroethylene, the number average molecular weight of the polytetrafluoroethylene being 3.0×10 6 The above is the binder for electrochemical devices.

[0009] The present disclosure (3) is the binder for electrochemical devices according to the present disclosure (2), wherein the water content is 0.050 mass % or less with respect to the polytetrafluoroethylene.

[0010] The present disclosure (4) is the binder for electrochemical devices according to the present disclosure (2) or (3), wherein the average aspect ratio of the primary particles of the polytetrafluoroethylene is 2.0 or less.

[0011] The present disclosure (5) is a binder for electrochemical devices in any combination with any of the present disclosures (2) to (4), wherein the polytetrafluoroethylene has an extrusion pressure of 50 MPa or less at a reduction ratio of 100.

[0012] The present disclosure (6) is a binder for electrochemical devices in any combination with any of the present disclosures (2) to (5), wherein the polytetrafluoroethylene is stretchable.

[0013] The present disclosure (7) is directed to a binder for electrochemical devices in any combination with any of the present disclosures (2) to (6) which are binders for batteries.

[0014] The present disclosure (8) is an electrode mixture comprising a binder for electrochemical devices, which is the polytetrafluoroethylene described in the present disclosure (1) or any combination of the polytetrafluoroethylene with any of the present disclosures (2) to (7), and an electrode active material.

[0015] The present disclosure (9) is the electrode mixture according to the present disclosure (8) which is a sheet.

[0016] The present disclosure (10) is an electrode comprising a binder for electrochemical devices, which is the polytetrafluoroethylene described in the present disclosure (1) or any combination of the polytetrafluoroethylene with any of the present disclosures (2) to (7), an electrode active material, and a current collector.

[0017] The present disclosure (11) is a secondary battery including the electrode according to the present disclosure (10). Effect of the Invention

[0018] According to the present disclosure, it is possible to provide polytetrafluoroethylene for binders for electrochemical devices, capable of forming an electrode mixture sheet having excellent strength, a binder for electrochemical devices, an electrode mixture, an electrode, and a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present disclosure will now be described in detail.

[0020] The present disclosure relates to polytetrafluoroethylene (PTFE) for use in a binder for an electrochemical device, the PTFE having a number average molecular weight of 3.0×10 6 The present invention provides the above-mentioned PTFE. Since the PTFE of the present disclosure has the above-mentioned configuration, it is possible to form an electrode mixture sheet having excellent strength. In addition, since it can be directly mixed with the electrode active material, it is not necessary to use an organic solvent, and the process and cost due to the use of the organic solvent can be reduced. Furthermore, since the PTFE of the present disclosure has excellent binding strength with the active material, the amount of use can be reduced.

[0021] The PTFE of the present disclosure has a number average molecular weight (Mn) of 3.0 × 10 6 The number average molecular weight is preferably 3.2×10 to form an electrode mixture sheet having higher strength. 6 More preferably, it is 3.5×10 or more. 6 More preferably, it is 3.7×10 or more. 6 More preferably, it is 4.0×10 or more. 6 It is particularly preferable that the number average molecular weight is 7.0×10 or more. 6 Preferably, it is 6.5×10 or less. 6 More preferably, it is 6.0×10 or less. 6 More preferably, it is 5.5×10 or less. 6 Even more preferably, it is 5.0×10 or less. 6 It is particularly preferred that: The number average molecular weight is a molecular weight calculated from the heat of crystallization estimated by measuring the temperature drop of a differential scanning calorimeter (DSC) after melting PTFE, according to the method described in the following document. The measurement is carried out five times, and the average value of the three values ​​excluding the maximum and minimum values ​​is used. Literature: Suwa, T.; Takehisa, M.; Machi, S., J. Appl. Polym. Sci. vol. 17, pp. 3253 (1973).

[0022] In terms of being able to form an electrode mixture sheet having even greater strength, the PTFE of the present disclosure preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on PTFE that has no history of being heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.

[0023] In terms of improving the moldability of the extrudate, the PTFE of the present disclosure has an extrusion pressure at a reduction ratio (RR) of 100 of preferably 50.0 MPa or less, more preferably 40.0 MPa or less, even more preferably 35.0 MPa or less, even more preferably 30.0 MPa or less, and particularly preferably 25.0 MPa or less. Moreover, the extrusion pressure is preferably 5.0 MPa or more, more preferably 10.0 MPa or more, even more preferably 12.0 MPa or more, and even more preferably 15.0 MPa or more, in that an electrode mixture sheet having even greater strength can be formed. The above extrusion pressure is a value determined by the following method. 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name: Isopar E, ExxonMobil) as an extrusion aid are mixed in a polyethylene container for 3 minutes. At room temperature (25±2°C), the above mixture is filled into the cylinder of an extruder, and a load of 0.47 MPa is applied to the piston inserted in the cylinder and held for 1 minute. The mixture is then extruded from the orifice at a ram speed of 18 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice (reduction ratio) is 100. In the latter half of the extrusion operation, the load (N) when the pressure reaches equilibrium is divided by the cross-sectional area of ​​the cylinder to determine the extrusion pressure (MPa).

[0024] The PTFE of the present disclosure is preferably expandable. In this specification, "expandable" is determined according to the following criteria. The bead obtained by paste extrusion with the RR100 described above is dried at 230°C for 30 minutes to remove the lubricant. The dried bead is cut to an appropriate length and placed in an oven heated to 300°C. In the oven, it is stretched at a stretching speed of 1000% / sec until it becomes 25 times the bead length before the stretching test. If it does not break during stretching, it is judged to be stretchable.

[0025] It is also preferable that the fluororesin of the present disclosure does not break during stretching in the above stretching test, even when stretched at a stretching speed of 100% / sec to a bead length 25 times that before the stretching test.

[0026] In terms of improving the binding force and electrode strength and enabling a further reduction in the extrusion pressure, the PTFE of the present disclosure has a standard specific gravity (SSG) of preferably 2.130 or more, more preferably 2.135 or more, and even more preferably 2.140 or more. Also, it is preferably 2.280 or less, more preferably 2.270 or less, even more preferably 2.260 or less, and even more preferably 2.250 or less. The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.

[0027] The PTFE of the present disclosure may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (modified monomer unit). In this specification, "modified PTFE" means a PTFE in which the content of polymerization units based on a modified monomer copolymerizable with TFE (modified monomer unit) is 1.0 mass% or less based on the total polymerization units. The content of TFE units in the modified PTFE may be 99.0 mass% or more. The modified PTFE may be composed of only TFE units and modified monomer units. The PTFE of the present disclosure is preferably a modified PTFE.

[0028] When the PTFE of the present disclosure is the modified PTFE, the content of the modified monomer units is 1.0% by mass or less based on the total polymerized units, but in terms of being able to reduce the extrusion pressure and increase the electrode strength, it is preferably 0.80% by mass or less, more preferably 0.50% by mass or less, even more preferably 0.40% by mass or less, even more preferably 0.30% by mass or less, even more preferably 0.20% by mass or less, even more preferably 0.10% by mass or less, even more preferably 0.08% by mass or less, particularly preferably 0.05% by mass or less, and most preferably 0.03% by mass or less. The content of the modified monomer unit may be 0.0001% by mass or more, 0.001% by mass or more, or 0.005% by mass or more, based on the total polymerized units. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0029] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0030] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene, perfluorovinyl ether, perfluoroallyl ether, (perfluoroalkyl)ethylene, ethylene, etc. The modified monomer used may be one type or multiple types.

[0031] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORf (A) (wherein Rf represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0032] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rf in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0033] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0034] The perfluorovinyl ether further includes those in which Rf in the above general formula (A) is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rf is the following formula:

[0035] [ka]

[0036] (wherein m represents 0 or an integer of 1 to 4), Rf is a group represented by the following formula:

[0037] [ka]

[0038] (wherein n represents an integer of 1 to 4).

[0039] The (perfluoroalkyl)ethylene (PFAE) is not particularly limited, and examples thereof include (perfluorobutyl)ethylene (PFBE) and (perfluorohexyl)ethylene.

[0040] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORf 1 (B) (In the formula, Rf 1 represents a perfluoro organic group.

[0041] Above Rf 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.

[0042] As the above-mentioned modifying monomer, at least one selected from the group consisting of VDF, HFP and PAVE is preferred, at least one selected from the group consisting of VDF and HFP is more preferred, and VDF is even more preferred, in that it is easy to adjust the number average molecular weight within the above-mentioned range.

[0043] The PTFE of the present disclosure generally has non-melt secondary processability. The non-melt secondary processability means that the melt flow rate cannot be measured at a temperature higher than the melting point in accordance with ASTM D-1238 and D-2116, in other words, that the PTFE does not flow easily even in the melting temperature range.

[0044] In the PTFE of the present disclosure, in the absence of a history of heating to a temperature of 300°C or higher, it is preferable that in a heat of fusion curve obtained by heating at a rate of 10°C / min using a differential scanning calorimeter [DSC], one or more endothermic peaks appear in the range of 320 to 350°C, and the heat of fusion at 290 to 350°C calculated from the heat of fusion curve is 50 mJ / mg or more.

[0045] The PTFE of the present disclosure may be a PTFE having a core-shell structure. For example, the PTFE having a core-shell structure may be a modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, such modified PTFE may be the PTFE described in JP-B-64-8022.

[0046] The PTFE of the present disclosure is preferably substantially free of moisture. This can suppress gas generation and deterioration of battery characteristics, and can also improve electrode strength. In addition, it is advantageous in terms of production process because it allows a wide range of electrode active materials to be combined. "Substantially free of moisture" means that the moisture content of the PTFE is 0.050% by mass or less. The water content is preferably 0.040% by mass or less, more preferably 0.030% by mass or less, even more preferably 0.010% by mass or less, even more preferably 0.005% by mass or less, and particularly preferably 0.002% by mass or less. The water content is measured by the following method. The mass of the PTFE is measured before and after heating at 150°C for 2 hours, and calculated according to the following formula. Samples are taken three times, and the mass is calculated for each time, and the average value is calculated and used. Moisture content (mass%) = [(mass of PTFE before heating (g)) - (mass of PTFE after heating (g))] / (mass of PTFE before heating (g)) x 100

[0047] The PTFE of the present disclosure is preferably substantially free of fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially free of fluorine-containing compounds" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is more preferably less than 25 ppb by mass, and even more preferably 10 ppb by mass or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0048] The amount of the fluorine-containing compound having a molecular weight of 1,000 or less is measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The resulting extract is concentrated using nitrogen purging as appropriate, and the fluorine-containing compounds in the concentrated extract are measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate fluorine-containing compound is confirmed. Prepare aqueous solutions with five or more levels of content of the standard substance, perform LC / MS analysis of the aqueous solutions with each content, plot the relationship between the content and the area for that content, and draw a calibration curve. Using the above calibration curve, the area of ​​the LC / MS chromatogram of the fluorine-containing compounds in the extract is converted to the content of the fluorine-containing compounds. The lower detection limit in this measurement method is 10 ppb by mass.

[0049] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include a fluorine-containing compound having a hydrophilic group and a molecular weight of 1000 g / mol or less. The molecular weight of the fluorine-containing compound is preferably 800 or less, and more preferably 500 or less. Polymer particles obtained by polymerization in the presence of a fluorine-containing surfactant usually contain a fluorine-containing surfactant in addition to PTFE. In this specification, the fluorine-containing surfactant is one that is used during polymerization. The above-mentioned fluorine-containing compound having a molecular weight of 1000 or less may be a compound that is not added during polymerization, for example, a compound that is generated as a by-product during polymerization. In addition, when the fluorine-containing compound having a molecular weight of 1000 or less contains an anionic moiety and a cationic moiety, it means a compound containing fluorine in which the molecular weight of the anionic moiety is 1000 or less. The fluorine-containing compound having a molecular weight of 1000 or less does not include PTFE.

[0050] The hydrophilic group may be, for example, -COOM, -SO2M, or -SO3M, where -COOM, -SO3M (in each formula, M is H, a metal atom, NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 1 is H or an organic group.

[0051] As the fluorine-containing surfactant, a surfactant containing fluorine (anionic fluorine-containing surfactant) whose anionic moiety has a molecular weight of 1000 or less can also be used. The "anionic moiety" refers to the part of the fluorine-containing surfactant excluding the cation. For example, F(CF2) n1 In the case of COOM, "F(CF2) n1 The "COO" part. The anionic fluorine-containing surfactant may be a surfactant represented by the following general formula (N 0 ): X n0 -Rf n0 -Y 0 (N 0 ) (In the formula, X n0 is H, Cl or F. n0 Y is a linear, branched or cyclic alkylene group having 3 to 20 carbon atoms, in which some or all of the H's are substituted with F, and the alkylene group may contain one or more ether bonds, and some of the H's may be substituted with Cl. 0 is an anionic group. Y 0 The anionic group may be -COOM, -SO2M, or -SO3M, and may be -COOM or -SO3M. M is H, a metal atom, or NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 1 is H or an organic group. The metal atom includes alkali metals (Group 1), alkaline earth metals (Group 2), etc., such as Na, K, or Li. R 1 As the 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be: M is H, a metal atom or NR 1 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4, which may be H, Na, K, Li or NH4. Above Rf n0 may be one in which 50% or more of H is substituted with fluorine.

[0052] The above fluorine-containing surfactant may be one type of fluorine-containing surfactant, or a mixture containing two or more types of fluorine-containing surfactants.

[0053] Examples of the fluorine-containing surfactant include compounds represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF2)7COOM, F(CF2)5COOM, H(CF2)6COOM, H(CF2)7COOM, CF3O(CF2)3OCHFCF2COOM, C3F7OCF(CF3)CF2OCF(CF3)COOM, CF3CF2CF2OCF(CF3)COOM, CF3CF2OCF2CF2OCF2COOM, C2F5OCF(CF3)CF2OCF(CF3)COOM, CF3OCF(CF3)CF2OCF(CF3)COOM, CF2ClCF2CF2OCF(CF3)CF2OCF2COOM, CF2ClCF2CF2OCF2CF(CF3)OCF2COOM, CF2ClCF(CF3)OCF(CF3)CF2OCF2COOM, CF2ClCF(CF3)OCF2CF(CF3)OCF2COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent. 1 is H or an organic group. The PTFE of the present disclosure is preferably substantially free of any of the fluorine-containing compounds represented by the above formulas.

[0054] In each of the above formulas, M is H, a metal atom, or NR 1 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4, which may be H, Na, K, Li or NH4. R 1 is H or C 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be:

[0055] When the PTFE of the present disclosure is substantially free of any of the fluorine-containing compounds represented by the above formulas, gas generation and deterioration of battery characteristics can be further suppressed, and the electrode strength can be further improved. "Substantially free of any of the fluorine-containing compounds represented by the above formulas" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably less than 25 ppb by mass, and more preferably 10 ppb by mass or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0056] The PTFE of the present disclosure has the following general formula: [C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14; M + represents a cation. It is also preferable that the electrolyte is substantially free of a fluorine-containing compound represented by the following formula (I): whereby gas generation and deterioration of battery characteristics can be further suppressed, and the electrode strength can be further improved. The cation M in the above formula + The M in the above is the same as M described above. "Substantially free of the fluorine-containing compound represented by the above formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably less than 25 ppb by mass, and more preferably 10 ppb by mass or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0057] The PTFE of the present disclosure is preferably in the form of a powder, and more preferably in the form of a fine powder.

[0058] The PTFE of the present disclosure has a high molecular weight, and in view of improving the binding strength and flexibility of the electrode, the average primary particle size is preferably 350 nm or less, more preferably 330 nm or less, even more preferably 320 nm or less, even more preferably 300 nm or less, especially preferably 280 nm or less, particularly preferably 250 nm or less, preferably 100 nm or more, more preferably 150 nm or more, even more preferably 170 nm or more, and particularly preferably 200 nm or more. The average primary particle size is measured by the following method. The PTFE aqueous dispersion is diluted with water until the solid content is 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph are measured to create a calibration curve. Using this calibration curve, the number-average particle diameter is determined from the measured transmittance of the 550 nm projected light of each sample, and is taken as the average primary particle diameter.

[0059] The PTFE of the present disclosure may have an average secondary particle size of 350 μm or more, preferably 400 μm or more, and more preferably 450 μm or more, and is preferably 1000 μm or less, more preferably 900 μm or less, even more preferably 800 μm or less, and even more preferably 700 μm or less. The average secondary particle size is measured in accordance with JIS K 6891.

[0060] In terms of excellent handleability, the PTFE of the present disclosure may have an average aspect ratio of primary particles of 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, even more preferably 1.6 or less, even more preferably 1.5 or less, even more preferably 1.4 or less, especially preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. The average aspect ratio may also be 1.0 or more. Incidentally, the PTFE having an average aspect ratio within the above range is usually a modified PTFE. The above average aspect ratio is determined by observing PTFE powder or an aqueous PTFE dispersion diluted to a solid content of approximately 1% by mass with a scanning electron microscope (SEM), processing the images of 200 or more particles randomly selected, and averaging the ratio of the long axis to the short axis.

[0061] In terms of excellent handleability, the PTFE of the present disclosure has an apparent density of preferably 0.40 g / ml or more, more preferably 0.43 g / ml or more, even more preferably 0.45 g / ml or more, even more preferably 0.48 g / ml or more, and particularly preferably 0.50 g / ml or more. The upper limit is not particularly limited, but may be 0.70 g / ml. The apparent density is measured in accordance with JIS K 6892.

[0062] The PTFE of the present disclosure can be produced, for example, by a production method including a step (A) of emulsion polymerizing TFE and, if necessary, a modifying monomer.

[0063] The above emulsion polymerization can be carried out, for example, in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator. The emulsion polymerization can be carried out by charging an aqueous medium, the anionic fluorine-containing surfactant, monomers and, if necessary, other additives into a polymerization reactor, stirring the contents of the reactor, maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of polymerization initiator to initiate the polymerization reaction. After the start of the polymerization reaction, monomers, polymerization initiators, chain transfer agents, the surfactants and the like may be additionally added depending on the purpose.

[0064] The polymerization initiator is not particularly limited as long as it can generate radicals within the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it can also be combined with a reducing agent or the like to initiate polymerization as a redox. The concentration of the polymerization initiator is appropriately determined depending on the type of monomer, the molecular weight of the desired PTFE, and the reaction rate.

[0065] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0066] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and disec-butyl peroxydicarbonate, peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate, dialkyl peroxides such as di-t-butyl peroxide, and the like. In addition, di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecafluorononanoyl) peroxide, di(perfluorobutyryl) peroxide, di(perfluorovaleryl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide, di(perfluorononanoyl) peroxide, di(ω-chloro Representative examples include di[perfluoro(or fluorochloro)acyl]peroxides such as di(ω-hexafluorobutyryl) peroxide, di(ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorodotriacontafluorodocosanoyl) peroxide.

[0067] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, or sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, or percarbonic acid, t-butyl permaleate, or t-butyl hydroperoxide, etc. A reducing agent such as sulfites or sulfites may also be contained, and the amount used may be 0.1 to 20 times that of the peroxide.

[0068] The amount of the water-soluble radical polymerization initiator to be added is not particularly limited, but may be added all at once, stepwise, or continuously in an amount (e.g., several ppm relative to water concentration) at least to the extent that the polymerization rate does not decrease significantly. The upper limit is a range in which the reaction temperature may be increased while removing heat from the equipment side by the polymerization reaction heat, and a more preferable upper limit is a range in which the polymerization reaction heat can be removed from the equipment side. In terms of easily obtaining the above-mentioned physical properties, the amount of the polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, and is preferably an amount equivalent to 100 ppm or less, more preferably an amount equivalent to 10 ppm or less, relative to the aqueous medium.

[0069] For example, when polymerization is carried out at a low temperature of 30° C. or less, it is preferable to use a redox initiator that combines an oxidizing agent and a reducing agent as the polymerization initiator. Examples of the oxidizing agent include persulfates, organic peroxides, potassium permanganate, manganese triacetate, cerium ammonium nitrate, and bromates. Examples of the reducing agent include sulfites, bisulfites, bromates, diimines, and oxalic acid. Examples of the persulfates include ammonium persulfate and potassium persulfate. Examples of the sulfites include sodium sulfite and ammonium sulfite. In order to increase the decomposition rate of the initiator, it is also preferable to add a copper salt or an iron salt to the combination of the redox initiator. Examples of the copper salt include copper(II) sulfate, and examples of the iron salt include iron(II) sulfate.

[0070] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, a persulfate, manganese triacetate, a cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof, or a diimine. More preferably, the oxidizing agent is permanganic acid or a salt thereof, a persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.

[0071] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate. When a redox initiator is used, either the oxidizing agent or the reducing agent may be charged in advance in a polymerization tank, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferable to charge ammonium oxalate in a polymerization tank and continuously add potassium permanganate thereto. In this specification, when the redox initiator is described as "potassium permanganate / ammonium oxalate," it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.

[0072] The redox initiator is particularly preferably a combination of an oxidizing agent that is a salt and a reducing agent that is a salt. For example, the oxidizing agent which is the salt is more preferably at least one selected from the group consisting of persulfates, permanganates, cerium (IV) salts, and bromates, further preferably permanganates, and particularly preferably potassium permanganate. The reducing agent which is the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.

[0073] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate, and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, and cerium ammonium nitrate / ammonium oxalate, and further preferably potassium permanganate / oxalic acid.

[0074] When a redox initiator is used, the oxidizing agent and the reducing agent may be added all at once at the beginning of the polymerization, the reducing agent may be added all at once at the beginning of the polymerization and the oxidizing agent may be added continuously, the oxidizing agent may be added all at once at the beginning of the polymerization and the reducing agent may be added continuously, or both the oxidizing agent and the reducing agent may be added continuously.

[0075] When one of the above redox polymerization initiators is added at the beginning of the polymerization and the other is added continuously, it is preferable to gradually reduce the rate of addition in order to obtain PTFE with a low SSG, and it is further preferable to stop the addition midway through the polymerization, and the timing for stopping the addition is preferably before 20 to 40 mass % of the total TFE consumed in the polymerization reaction is consumed.

[0076] When a redox initiator is used as a polymerization initiator, the amount of the oxidizing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, more preferably 5 ppm or more, even more preferably 10 ppm or more, and more preferably 10000 ppm or less, more preferably 1000 ppm or less, more preferably 100 ppm or less, and even more preferably 10 ppm or less. The amount of the reducing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, more preferably 5 ppm or more, even more preferably 10 ppm or more, and more preferably 10000 ppm or less, more preferably 1000 ppm or less, more preferably 100 ppm or less, and even more preferably 10 ppm or less. When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100° C. or lower, more preferably 95° C. or lower, and even more preferably 90° C. or lower. The polymerization temperature is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher.

[0077] As the polymerization initiator, a water-soluble radical polymerization initiator and a redox initiator are preferred in terms of improving the binding force, electrode strength, and electrode flexibility.

[0078] The aqueous medium is a reaction medium for polymerization, and refers to a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and, for example, a fluorine-free organic solvent such as an alcohol, ether, or ketone, and / or a fluorine-containing organic solvent having a boiling point of 40° C. or less.

[0079] In the above emulsion polymerization, a nucleating agent, a chain transfer agent, a buffering agent, a pH adjusting agent, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposing agent for the polymerization initiator, and the like may be used, if necessary.

[0080] The emulsion polymerization is preferably carried out with the addition of a nucleating agent for the purpose of adjusting the particle size. The nucleating agent is preferably added before the start of the polymerization reaction. As the nucleating agent, a known agent can be used. For example, it is preferable that the nucleating agent is at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents, and it is more preferable that the nucleating agent is a nonionic surfactant.

[0081] The fluoropolyether may, for example, be a perfluoropolyether (PFPE) acid or a salt thereof. The perfluoropolyether (PFPE) acid or salt thereof may have any chain structure in which oxygen atoms in the backbone of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. Also, two or more types of fluorocarbon groups may be present in the molecule. A representative structure has a repeating unit represented by the following formula: (-CFCF3-CF2-O-) n (-CF2-CF2-CF2-O-) n (-CF2-CF2-O-) n -(-CF2-O-) m (-CF2-CFCF3-O-) n -(-CF2-O-) m

[0082] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed therein, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. The PFPE acid or its salt may also have a sulfonic acid, phosphonic acid group or their salt at one or both ends. The PFPE acid or its salt may also have a different group at each end. For monofunctional PFPEs, the other end of the molecule is usually perfluorinated, but may contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least two ether oxygens, preferably at least four ether oxygens, and even more preferably at least six ether oxygens. Preferably, at least one of the fluorocarbon groups separating the ether oxygens, more preferably at least two of such fluorocarbon groups, has two or three carbon atoms. Even more preferably, at least 50% of the fluorocarbon groups separating the ether oxygens have 2 or 3 carbon atoms. Also preferably, the PFPE acid or salt thereof has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure above is at least 5. Two or more of the PFPE acids or salts thereof having an acid group at one or both termini may be used in the manufacturing method of the present disclosure. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.

[0083] The emulsion polymerization is preferably carried out by adding a radical scavenger or a decomposer of the polymerization initiator, since it can further increase the molecular weight of PTFE and improve the strength of the electrode mixture sheet. The radical scavenger or the decomposer of the polymerization initiator is preferably added after the start of the polymerization reaction, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and preferably before 50% by mass or less, preferably 40% by mass or less is polymerized. When depressurizing and repressurizing as described below are performed, it is preferable to add it after that.

[0084] The radical scavenger is a compound that does not have the ability to restart after addition or chain transfer to the free radical in the polymerization system. Specifically, a compound that easily undergoes a chain transfer reaction with a primary radical or a growing radical, and then generates a stable radical that does not react with a monomer, or a compound that easily undergoes an addition reaction with a primary radical or a growing radical, and generates a stable radical, is used. Generally, the activity of what is called a chain transfer agent is characterized by the chain transfer constant and the reinitiation efficiency, but among chain transfer agents, those with a reinitiation efficiency of almost 0% are called radical scavengers. The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero percent. "Reinitiation efficiency is substantially zero percent" means that the generated radicals turn the radical scavenger into stable radicals. Preferably, the compound has a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) of more than 0.1. The above compound has a chain transfer constant (Cs) of more preferably 0.5 or more, even more preferably 1.0 or more, even more preferably 5.0 or more, and particularly preferably 10 or more.

[0085] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl2). Examples of the aromatic hydroxy compound include unsubstituted phenol, polyhydric phenol, salicylic acid, m- or p-salicylic acid, gallic acid, and naphthol. The unsubstituted phenols include o-, m-, or p-nitrophenol, o-, m-, or p-aminophenol, p-nitrosophenol, etc. The polyhydric phenols include catechol, resorcinol, hydroquinone, pyrogallol, phloroglucinol, naphthresorcinol, etc. Examples of aromatic amines include o-, m- or p-phenylenediamine, benzidine, and the like. Examples of the quinone compound include o-, m- or p-benzoquinone, 1,4-naphthoquinone, alizarin, and the like. Examples of thiocyanates include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN). Of the above radical scavengers, aromatic hydroxy compounds are preferred, unsubstituted phenols or polyhydric phenols are more preferred, and hydroquinone is even more preferred.

[0086] The amount of the radical scavenger added is preferably an amount equivalent to 3 to 500% (molar basis) of the polymerization initiator concentration from the viewpoint of appropriately reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).

[0087] The decomposer for the polymerization initiator may be any compound capable of decomposing the polymerization initiator used, and is preferably at least one selected from the group consisting of sulfites, bisulfites, bromates, diimines, diimine salts, oxalic acid, oxalates, copper salts, and iron salts. Examples of sulfites include sodium sulfite and ammonium sulfite. Examples of copper salts include copper(II) sulfate, and examples of iron salts include iron(II) sulfate. The amount of the decomposition agent added is preferably an amount equivalent to 3 to 500% (molar basis) of the initiator concentration from the viewpoint of appropriately reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).

[0088] In the above emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined depending on the type of monomer used, the molecular weight of the target PTFE, and the reaction rate. Usually, the polymerization temperature is 5 to 150°C, preferably 10°C or higher, more preferably 30°C or higher, and even more preferably 50°C or higher. Also, it is more preferably 120°C or lower, and even more preferably 100°C or lower. The polymerization pressure is 0.05 to 10 MPaG. The polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. Also, the polymerization pressure is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.

[0089] When VDF is used as the modified monomer, in the emulsion polymerization, the VDF concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, in order to easily obtain the above-mentioned physical properties. The concentration may be 15 mol% or less, preferably 6.0 mol% or less, more preferably 5.0 mol% or less, even more preferably 3.0 mol% or less, and particularly preferably 1.0 mol% or less. The VDF concentration may be maintained until the end of the polymerization reaction, or depressurization may be performed during the reaction. It is preferable to charge VDF all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0090] When VDF is used as the modified monomer, it is preferable not to release the pressure in the emulsion polymerization after VDF is charged into the polymerization vessel until the polymerization is completed. This allows VDF to remain in the system until the end of the polymerization, and the strength of the resulting electrode mixture sheet using PTFE can be further increased.

[0091] When HFP is used as the modified monomer, in the emulsion polymerization, the HFP concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.01 to 3.0 mol % in order to easily obtain the above-mentioned properties. Furthermore, the HFP concentration in the gas in the reactor at the time when 40 mass % of the total TFE consumed in the polymerization reaction is polymerized is preferably greater than 0 mol % and 0.2 mol % or less. The above HFP concentration is preferably maintained until the end of the polymerization reaction. HFP may be charged all at once before the start of polymerization, or a portion may be charged before the start of polymerization and added continuously or intermittently after the start of polymerization. By allowing HFP to remain until the end of the polymerization reaction, the extrusion pressure is reduced even though the strength of the electrode mixture sheet using the obtained PTFE is high.

[0092] When HFP is used as the modified monomer, in the above emulsion polymerization, it is preferable to release the pressure before 5 to 40 mass% of the total TFE consumed in the polymerization reaction is polymerized, and then re-pressurize using only TFE, in order to further improve the strength of the resulting electrode mixture sheet using PTFE. The pressure reduction is preferably carried out so that the pressure inside the reactor is 0.2 MPaG or less, more preferably 0.1 MPaG or less, and even more preferably 0.05 MPaG or less. Also, it is preferably carried out so that the pressure inside the reactor is 0.0 MPaG or more. The above pressure reduction and re-increase may be carried out several times. The pressure reduction may be carried out until the pressure is reduced using a vacuum pump.

[0093] When CTFE is used as the modified monomer, the CTFE concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, in terms of easily obtaining each of the above-mentioned physical properties. The above concentration is also preferably 3.0 mol% or less, more preferably 1.0 mol% or less. The above CTFE concentration may be maintained until the end of the polymerization reaction, or depressurization may be performed during the reaction. CTFE is preferably charged all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0094] When CTFE is used as the modified monomer, it is preferable not to release the pressure in the emulsion polymerization after CTFE is charged into the polymerization vessel until the polymerization is completed. This allows CTFE to remain in the system until the end of the polymerization, and the strength of the electrode mixture sheet using the obtained fluororesin can be further increased.

[0095] When PMVE is used as the modified monomer, the PMVE concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.005 mol% or more, and even more preferably 0.01 mol% or more, in terms of easily obtaining the above-mentioned physical properties. The above concentration is also preferably 3.0 mol% or less, more preferably 1.0 mol% or less. The above PMVE concentration may be maintained until the end of the polymerization reaction, or depressurization may be carried out during the reaction. PMVE is preferably charged all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0096] When PMVE is used as the modified monomer, it is preferable not to release the pressure in the emulsion polymerization after the PMVE is charged into the polymerization vessel until the polymerization is completed, so that the PMVE can be left in the system until the end of the polymerization, and the strength of the obtained electrode mixture sheet using the fluororesin can be further increased.

[0097] The above-mentioned production method may include a step (B) of coagulating the above-mentioned aqueous dispersion to obtain the above-mentioned wet powder of PTFE. The above-mentioned coagulation can be carried out by a known method.

[0098] The above-mentioned manufacturing method may include a step (C) of drying the above-mentioned wet powder. The above-mentioned drying is usually carried out by using a means such as vacuum, high frequency, or hot air while keeping the above-mentioned wet powder in a state where it is not very fluid, preferably in a state where it is left stationary. Friction between powders, especially at high temperatures, generally has an undesirable effect on fine powder-type PTFE. This is because particles made of this type of PTFE have the property of easily fibrillating even with a small shear force and losing the original stable particle structure state. The drying temperature is preferably 300° C. or less, more preferably 250° C. or less, even more preferably 230° C. or less, even more preferably 210° C. or less, even more preferably 190° C. or less, and particularly preferably 170° C. or less, from the viewpoint of reducing the extrusion pressure. From the viewpoint of improving the breaking strength, the temperature is preferably 10° C. or more, more preferably 100° C. or more, even more preferably 150° C. or more, even more preferably 170° C. or more, even more preferably 190° C. or more, and particularly preferably 210° C. or more. In order to further increase the strength ratio, it is preferable to appropriately adjust the temperature within this temperature range.

[0099] The step (C) is preferably a step of placing the wet powder in a container whose bottom and / or sides are air permeable, and heat-treating the wet powder for 2 hours or more at a temperature of 150 to 300° C. By carrying out heat treatment under such extremely limited conditions, the fluorine-containing compound having a molecular weight of 1000 or less can be efficiently removed together with water, and the contents of the fluorine-containing compound and water can be within the above-mentioned ranges.

[0100] The temperature of the heat treatment in step (C) is preferably 160°C or higher, more preferably 180°C or higher, even more preferably 200°C or higher, particularly preferably 220°C or higher, and is preferably 280°C or lower, in order to more efficiently remove moisture and fluorine-containing compounds.

[0101] The time for the heat treatment in step (C) is preferably 5 hours or more, more preferably 10 hours or more, and even more preferably 15 hours or more, in terms of more efficiently removing moisture and fluorine-containing compounds. The upper limit is not particularly limited, but is, for example, preferably 100 hours, more preferably 50 hours, and even more preferably 30 hours.

[0102] The wind speed in step (C) is preferably 0.01 m / s or more, more preferably 0.03 m / s or more, even more preferably 0.05 m / s or more, and even more preferably 0.1 m / s or more, from the viewpoint of more efficiently removing moisture and fluorine-containing compounds, and is preferably 50 m / s or less, more preferably 30 m / s or less, and even more preferably 10 m / s or less, from the viewpoint of suppressing scattering of powder.

[0103] The heat treatment in step (C) can be carried out using an electric furnace or a steam furnace. For example, it can be carried out using electric furnaces such as a parallel flow box type electric furnace, a ventilated box type electric furnace, a ventilated conveyor type electric furnace, a band electric furnace, a radiant conveyor type electric furnace, a fluidized bed electric furnace, a vacuum electric furnace, an agitation type electric furnace, an airflow type electric furnace, a hot air circulation type electric furnace, or a steam furnace corresponding to the above (a device in which the electric furnace in the device name of each electric furnace is replaced with a steam furnace). In terms of being able to remove moisture and fluorine-containing compounds more efficiently, a parallel flow box type electric furnace, a ventilated box type electric furnace, a ventilated conveyor type electric furnace, a band electric furnace, a fluidized bed electric furnace, a hot air circulation type electric furnace, or a steam furnace corresponding to the above (a device in which the electric furnace in the device name of each electric furnace is replaced with a steam furnace) is preferred.

[0104] The heat treatment in step (C) is carried out by placing the wet powder in a container with air permeability at the bottom and / or sides. The container with air permeability at the bottom and / or sides may be any container that can withstand the heat treatment temperature, and is preferably made of a metal such as stainless steel. The container having breathable bottom and / or sides is preferably a tray (bat) having breathable bottom and / or sides, and more preferably a tray having a mesh bottom and / or sides (mesh tray). The mesh is preferably either a woven mesh or a punched metal. The mesh size is preferably 2000 μm or less (ASTM standard 10 mesh or more), more preferably 595 μm or less (30 mesh or more), even more preferably 297 μm or less (50 mesh or more), even more preferably 177 μm or less (80 mesh or more), particularly preferably 149 μm or less (100 mesh or more), and particularly preferably 74 μm or less (200 mesh or more). Also, 25 μm or more (500 mesh or less) is preferable. When the mesh is a woven net, the weaving method may be, for example, plain weave, twill weave, plain tatami weave, or twill tatami weave. When the mesh is a punched metal, the aperture ratio is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more, and is preferably 95% or less.

[0105] In the step (C), the amount of the moist powder to be placed is preferably 10 g / cm from the viewpoint of more efficiently removing moisture and fluorine-containing compounds. 2 It is preferable that the thickness is less than 8 g / cm 2 More preferably, it is 5 g / cm or less. 2 More preferably, it is 3 g / cm or less. 2 It is particularly preferable that the density is 0.01 g / cm or less. 2 It is preferable that the concentration is 0.05 g / cm or more. 2 More preferably, it is 0.1 g / cm or more. 2 More preferably, it is equal to or greater than this.

[0106] The moisture content of the moist powder to be heat-treated in step (C) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, relative to the moist powder, in order to more efficiently remove moisture and fluorine-containing compounds, and is preferably 150% by mass or less, and more preferably 100% by mass or less.

[0107] The PTFE of the present disclosure is used in a binder for electrochemical devices. In the binder for electrochemical devices, the PTFE of the present disclosure may be used alone or may be mixed with other materials (e.g., polymers other than the PTFE of the present disclosure), but it is preferable to use the PTFE of the present disclosure substantially alone, and more preferable to use it alone. Note that using the PTFE of the present disclosure substantially alone means that the amount of the PTFE of the present disclosure in the binder for electrochemical devices is used within the range described below.

[0108] The present disclosure relates to a binder for electrochemical devices that is substantially composed of PTFE, and the PTFE has a number average molecular weight of 3.0×10 6 The present invention also provides the above-mentioned binder for electrochemical devices. The binder of the present disclosure contains a specific PTFE, so that an electrode mixture sheet having excellent strength can be formed. In addition, since it can be directly mixed with the electrode active material, it is not necessary to use an organic solvent, so that the process and cost due to the use of the organic solvent can be reduced. Furthermore, since the binder of the present disclosure has excellent binding strength with the active material, the amount of the binder used can be reduced.

[0109] As the PTFE in the binder of the present disclosure, the same PTFE as that of the present disclosure described above can be used, and the preferred embodiments are also the same.

[0110] The binder of the present disclosure is substantially composed of the PTFE. This allows the effects of the PTFE to be significantly exhibited. "Substantially composed of the PTFE" means that the content of the PTFE is 95.0% by mass or more relative to the binder. The content of the PTFE relative to the binder is preferably 98.0% by mass or more, more preferably 99.0% by mass or more, even more preferably 99.5% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more. It is also preferred that the binder of the present disclosure consists solely of the above-mentioned PTFE.

[0111] The binder of the present disclosure is preferably substantially free of organic solvent. This can reduce the steps and costs involved in using organic solvents. "Substantially free of organic solvent" means that the organic solvent content of the binder is 5% by mass or less. The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.

[0112] The binder of the present disclosure is preferably in the form of a powder.

[0113] The binders of the present disclosure are used in electrochemical devices such as batteries and capacitors. The battery may be a secondary battery such as a lithium ion battery. The capacitor is not particularly limited, but is preferably an electrochemical capacitor. Examples of the electrochemical capacitor include an electric double layer capacitor, a hybrid capacitor, and a redox capacitor. Examples of the hybrid capacitor include a sodium ion capacitor, a lithium ion capacitor, and a magnesium ion capacitor. Among these, an electric double layer capacitor is particularly preferred.

[0114] The binder of the present disclosure can be suitably used as a binder for batteries, and can be particularly suitably used as a binder for secondary batteries such as lithium ion batteries. The binders of the present disclosure may be used to fabricate electrochemical device components, preferably battery components. The binder of the present disclosure can be particularly suitably used as a binder for electrodes. The binder of the present disclosure can also be suitably used as a binder in the solid electrolyte layer of a solid secondary battery.

[0115] The present disclosure also provides an electrode mixture comprising the above-mentioned PTFE of the present disclosure or the binder for electrochemical devices of the present disclosure and an electrode active material. The electrode mixture of the present disclosure has excellent sheet strength. By using the electrode mixture of the present disclosure, an electrode with excellent strength can be obtained. In addition, even if the amount of binder is small, the electrode active material can be held.

[0116] The electrode active material includes a positive electrode active material and a negative electrode active material.

[0117] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide, an alkali metal-containing transition metal phosphate compound, and a conductive polymer. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces a high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, and potassium ion. In a preferred embodiment, the alkali metal ion may be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.

[0118] Examples of the alkali metal-containing transition metal composite oxide include: Formula:M a Mn 2-b M1 b O4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 and alkali metal-cobalt composite oxides (lithium-cobalt composite oxides, etc.) represented by the formula (I) (wherein M is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge). In the above, M is preferably one metal selected from the group consisting of Li, Na, and K, more preferably Li or Na, and even more preferably Li.

[0119] Among these, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are the most popular because they can provide high energy density and high output secondary batteries. 0.8 Co 0.15 Al 0.05 O2 or MNi 1 / 3 Co 1 / 3 Mn1 / 3 O2 and the like are preferred, and a compound represented by the following general formula (3) is preferred. MNi h Co i Mn j M 5 k O2(3) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0120] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following formula (4): M e M 4 f (PO4) g (4) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li. That is, the alkali metal-containing transition metal phosphate compound is preferably a lithium-containing transition metal phosphate compound.

[0121] The transition metal of the lithium-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. The lithium-containing transition metal phosphate compound is preferably one having an olivine structure.

[0122] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3, etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 A positive electrode active material such as O2 is preferable because the crystal structure does not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or more. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the above-mentioned positive electrode active material is preferable because the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change even when stored at high temperatures, and the battery performance is not deteriorated even when operated at high voltages.

[0123] Other positive electrode active materials include M2MnO3 and MM 6 O2 (wherein M is at least one metal selected from the group consisting of Li, Na, and K; M 6 Also included are solid solution materials with transition metals such as Co, Ni, Mn, and Fe.

[0124] The solid solution material can be, for example, a material having the general formula Mx[Mn (1-y) M 7 y ]O zIt is an alkali metal manganese oxide represented by the formula. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn. For example, it contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the ranges of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 A manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-solved based on Li2MnO3 such as O2 is preferable because it can provide an alkali metal ion secondary battery having a high energy density.

[0125] Also, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. There is no limitation on the use of lithium phosphate, but it is preferably used by mixing it with the above positive electrode active material. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and still more preferably 0.5% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and still more preferably 5% by mass or less, based on the total of the above positive electrode active material and lithium phosphate.

[0126] Examples of the conductive polymer include p-doped type conductive polymers and n-doped type conductive polymers. Examples of the conductive polymer include polyacetylene-based, polyphenylene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, and the like.

[0127] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0128] These surface-attaching substances can be attached to the surface of the positive electrode active material by, for example, a method of dissolving or suspending in a solvent, impregnating and adding to the positive electrode active material, and drying, a method of dissolving or suspending a surface-attaching substance precursor in a solvent, impregnating and adding to the positive electrode active material, and then reacting by heating, etc., a method of adding to a positive electrode active material precursor and simultaneously baking, etc. When carbon is attached, a method of mechanically attaching carbonaceous material in the form of, for example, activated carbon, etc., afterwards can also be used.

[0129] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more, and preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less, as a lower limit, by mass relative to the positive electrode active material. The surface-attached substance can suppress the oxidation reaction of the electrolyte on the surface of the positive electrode active material, and can improve the battery life, but if the amount of attachment is too small, the effect is not fully manifested, and if it is too large, the ingress and egress of lithium ions is inhibited, and resistance may increase.

[0130] The shape of the particles of the positive electrode active material may be any of the conventional shapes such as block, polyhedron, sphere, oval sphere, plate, needle, column, etc. Primary particles may be aggregated to form secondary particles.

[0131] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3That is all. If the tap density of the positive electrode active material is below the lower limit, the amount of dispersion medium required during the formation of the positive electrode active material layer increases, and the amount of conductive material and binder required also increases, which may restrict the filling rate of the positive electrode active material in the positive electrode active material layer and restrict the battery capacity. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally, the higher the tap density, the better, and there is no particular upper limit. However, if the tap density is too high, the diffusion of lithium ions in the positive electrode active material layer using the electrolyte as a medium becomes rate-limiting, and the load characteristics may be easily deteriorated, so the upper limit is preferably 4.0 g / cm. 3 Less than or equal to 3.7 g / cm 3 More preferably, 3.5 g / cm 3 The following is the result. The above tap density is the powder packing density (tap density) g / cm when 5 to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and tapped 200 times with a stroke of approximately 20 mm. 3 is required.

[0132] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter when primary particles are aggregated to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, even more preferably 0.8 μm or more, and most preferably 1.0 μm or more, and is preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, and most preferably 22 μm or less. If it is below the lower limit, a high tap density product may not be obtained, and if it exceeds the upper limit, it may take time for lithium to diffuse within the particles, resulting in a decrease in battery performance, or problems such as streaking may occur when preparing the positive electrode of a battery, that is, when the active material, conductive material, binder, etc. are slurried with a solvent and applied in a thin film. Here, by mixing two or more types of the above positive electrode active materials having different median diameters d50, the filling property during the preparation of the positive electrode can be further improved.

[0133] The median diameter d50 is measured by a known laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used as the dispersion medium for the measurement, and the measurement refractive index is set to 1.24 after ultrasonic dispersion for 5 minutes.

[0134] In the case where the primary particles are aggregated to form secondary particles, the average primary particle diameter of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which may adversely affect the powder packing property or greatly reduce the specific surface area, and therefore the battery performance such as output characteristics may be likely to decrease. On the other hand, if the lower limit is exceeded, problems such as poor reversibility of charge and discharge may occur due to underdeveloped crystals. The average primary particle diameter is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph at a magnification of 10,000 times, the longest intercept value of a horizontal line at the left and right boundaries of a primary particle is determined for any 50 primary particles, and the average value is calculated.

[0135] The BET specific surface area of ​​the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, whereas if it is larger, it is difficult to increase the tap density, and problems may easily occur in the application property when forming the positive electrode active material layer. The BET specific surface area is defined as a value measured by a nitrogen adsorption BET one-point method using a gas flow method, using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.) after pre-drying a sample at 150°C for 30 minutes under a nitrogen flow and then using a nitrogen / helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.

[0136] When the secondary battery of the present disclosure is used as a large-sized lithium-ion secondary battery for hybrid vehicles or distributed power sources, high output is required, so it is preferable that the particles of the positive electrode active material are mainly secondary particles. The particles of the positive electrode active material preferably have an average secondary particle diameter of 40 μm or less and contain 0.5 to 7.0 volume % of fine particles having an average primary particle diameter of 1 μm or less. By containing fine particles having an average primary particle diameter of 1 μm or less, the contact area with the electrolyte increases, and the diffusion of lithium ions between the electrode mixture and the electrolyte can be made faster, resulting in improved output performance of the battery.

[0137] The manufacturing method of the positive electrode active material is a general method for manufacturing inorganic compounds.In particular, various methods can be considered for making spherical or elliptical active materials, for example, the raw material of transition metal is dissolved or crushed and dispersed in a solvent such as water, and the pH is adjusted while stirring to make and recover spherical precursors, which are dried as necessary, and then LiOH, Li2CO3, LiNO3, or other Li sources are added and calcined at high temperature to obtain active materials.

[0138] For the production of the positive electrode, the positive electrode active material may be used alone, or two or more of different compositions may be used in any combination or ratio. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Examples of such a combination include a combination with a ternary system such as O2, a combination of LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced with another transition metal, or a combination of LiFePO4 and LiCoO2 or a combination in which a portion of the Co is replaced with another transition metal.

[0139] The content of the positive electrode active material is preferably 50 to 99.5% by mass of the positive electrode mixture, more preferably 80 to 99% by mass, in terms of high battery capacity. The content in the positive electrode active material layer is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. The upper limit is preferably 99% by mass or less, more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the strength of the positive electrode may be insufficient.

[0140] The negative electrode active material is not particularly limited, and examples thereof include lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and carbonaceous materials such as non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, Li4Ti5O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0141] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By using the negative electrode active material containing silicon as a constituent element, a high-capacity battery can be produced.

[0142] The silicon-containing material is preferably silicon particles, particles having a structure in which fine silicon particles are dispersed in a silicon-based compound, silicon oxide particles represented by the general formula SiOx (0.5≦x≦1.6), or a mixture thereof. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a high capacity, and excellent cycle characteristics can be obtained.

[0143] Silicon oxide in the present disclosure is a general term for amorphous silicon oxide, and silicon oxide before disproportionation is represented by the general formula SiOx (0.5≦x≦1.6). x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, which is then cooled and precipitated.

[0144] Particles having a structure in which silicon particles are dispersed in a silicon-based compound can be obtained, for example, by a method of baking a mixture of silicon particles and a silicon-based compound, or by heat treating silicon oxide particles before disproportionation represented by the general formula SiOx in an inert non-oxidizing atmosphere such as argon at a temperature of 400°C or higher, preferably 800 to 1,100°C, to perform a disproportionation reaction. In particular, the material obtained by the latter method is preferable because the silicon microcrystals are uniformly dispersed. The size of the silicon nanoparticles can be made 1 to 100 nm by the above-mentioned disproportionation reaction. Note that the silicon oxide in the particles having a structure in which silicon nanoparticles are dispersed in silicon oxide is preferably silicon dioxide. Note that it is possible to confirm that silicon nanoparticles (crystals) are dispersed in amorphous silicon oxide by a transmission electron microscope.

[0145] The physical properties of the silicon-containing particles can be appropriately selected depending on the composite particles to be produced. For example, the average particle size is preferably 0.1 to 50 μm, and the lower limit is more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. The upper limit is more preferably 30 μm or less, and even more preferably 20 μm or less. The average particle size is expressed as the weight average particle size measured by a particle size distribution measurement using a laser diffraction method.

[0146] BET specific surface area is 0.5 to 100 m 2 / g is preferable, and 1 to 20m 2 / g is more preferable. 2 If the content is 100 m / g or more, there is no risk of the adhesiveness decreasing when applied to an electrode, resulting in a decrease in battery characteristics. 2 / g or less, the proportion of silicon dioxide on the particle surface becomes large, and there is no risk of a decrease in battery capacity when used as a negative electrode material for a lithium ion secondary battery.

[0147] The silicon-containing particles are coated with carbon to impart electrical conductivity, which leads to improved battery characteristics. Methods for imparting electrical conductivity include mixing the silicon-containing particles with conductive particles such as graphite, coating the surfaces of the silicon-containing particles with a carbon coating, and combining both of these methods. The carbon coating method is preferred, and chemical vapor deposition (CVD) is more preferred.

[0148] In order to increase the capacity of the resulting electrode mixture, the content of the negative electrode active material is preferably 40% by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more in the electrode mixture, and the upper limit is preferably 99% by mass or less, more preferably 98% by mass or less.

[0149] The electrode mixture of the present disclosure preferably further contains a conductive assistant. Any known conductive material can be used as the conductive assistant. Specific examples include metal materials such as copper and nickel, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF. These may be used alone or in any combination and ratio of two or more.

[0150] The conductive assistant is used in an electrode mixture so that it is contained in an amount of usually 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more, and usually 50% by mass or less, preferably 30% by mass or less, more preferably 15% by mass or less. If the content is lower than this range, the conductivity may be insufficient. Conversely, if the content is higher than this range, the battery capacity may decrease.

[0151] The electrode mixture of the present disclosure may further contain a thermoplastic resin. Examples of the thermoplastic resin include polyvinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, polyethylene oxide, etc. One type may be used alone, or two or more types may be used in any combination and ratio.

[0152] The ratio of the thermoplastic resin to the electrode active material is usually 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and usually 3.0% by mass or less, preferably 2.5% by mass or less, more preferably 2.0% by mass or less. The addition of the thermoplastic resin can improve the mechanical strength of the electrode. If the ratio exceeds this range, the ratio of the electrode active material in the electrode mixture decreases, which may cause problems such as a decrease in the battery capacity or an increase in the resistance between the active materials.

[0153] In the electrode mixture of the present disclosure, the content of the binder may be 0.1% by mass or more, preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and may be 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 10% by mass or less, particularly preferably 5% by mass or less, and most preferably 3% by mass or less. If the proportion of the binder is too low, the electrode mixture active material cannot be sufficiently held, and the mechanical strength of the electrode mixture sheet may be insufficient, which may deteriorate the battery performance such as cycle characteristics. On the other hand, if the proportion is too high, it may lead to a decrease in battery capacity and conductivity. Since the binder of the present disclosure has excellent binding strength, even if the content is small, the electrode active material can be sufficiently held.

[0154] In the electrode mixture of the present disclosure, the binder component is preferably substantially composed of the PTFE, and more preferably is composed of the PTFE. The binder component is substantially composed of the PTFE, which means that the content of the PTFE in the binder component constituting the electrode mixture is 95.0% by mass or more relative to the binder component. The content of the PTFE is preferably 98.0% by mass or more relative to the binder component, more preferably 99.0% by mass or more, even more preferably 99.5% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more.

[0155] The electrode mixture of the present disclosure is preferably in the form of a sheet.

[0156] The electrode mixture of the present disclosure can be suitably used as an electrode mixture for a secondary battery. In particular, the electrode mixture of the present disclosure is suitable for a lithium ion secondary battery. When used in a secondary battery, the electrode mixture of the present disclosure is usually used in a sheet form.

[0157] The manufacturing method of the electrode mixture sheet is not limited, but a specific example of the manufacturing method will be described below.

[0158] Step (a): mixing a powder component and a binder to form an electrode mixture; Step (b): Calendaring or extrusion molding the electrode mixture to produce a sheet; Including, The mixing in step (a) is (a1) homogenizing the powder components and the binder to form a powder; (a2) mixing the powdered raw material mixture obtained in step (a1) to prepare an electrode mixture; It is preferable that the production method is characterized by comprising the steps of:

[0159] For example, PTFE has two transition temperatures at about 19°C and about 30°C. Below 19°C, PTFE can be easily mixed while still maintaining its shape. However, above 19°C, the structure of the PTFE particles becomes loose and more sensitive to mechanical shear. At temperatures above 30°C, a greater degree of fibrillation occurs.

[0160] For this reason, the homogenization in (a1) is preferably carried out at a temperature of 19°C or lower, preferably from 0°C to 19°C. That is, in such (a1), it is preferable to mix and homogenize while suppressing fibrillation. The subsequent mixing step (a2) is preferably carried out at a temperature of 30° C. or higher to promote fibrillation.

[0161] The above step (a2) is carried out at a temperature of preferably 30°C to 150°C, more preferably 35°C to 120°C, and even more preferably 40°C to 80°C. In one embodiment, the calendaring or extrusion of step (b) above is carried out at a temperature between 30°C and 150°C, preferably between 35°C and 120°C, more preferably between 40°C and 100°C.

[0162] The mixing in the above step (a) is preferably carried out while applying a shear force. Specific mixing methods include methods using a W-type mixer, V-type mixer, drum mixer, ribbon mixer, conical screw mixer, single-shaft kneader, twin-shaft kneader, Mix Muller, stirring mixer, planetary mixer, Henschel mixer, high-speed mixer, etc.

[0163] The mixing conditions may be appropriately set by the number of revolutions and the mixing time. For example, the number of revolutions is preferably 15,000 rpm or less. It is preferably 10 rpm or more, more preferably 1,000 rpm or more, and even more preferably 3,000 rpm or more, and is preferably 12,000 rpm or less, more preferably 11,000 rpm or less, and even more preferably 10,000 rpm. If it is below the above range, it will take a long time to mix, which will affect productivity. If it is above the above range, fibrillation will proceed excessively, and the electrode mixture sheet may have poor strength. The step (a1) is preferably carried out with a weaker shear force than the step (a2).

[0164] In the above step (a2), the raw material composition preferably does not contain a liquid solvent, but a small amount of a lubricant may be used. That is, a lubricant may be added to the powdered raw material mixture obtained in the above step (a1) to prepare a paste.

[0165] The lubricant is not particularly limited, and examples thereof include water, ether compounds, alcohols, ionic liquids, carbonates, aliphatic hydrocarbons (low polarity solvents such as heptane and xylene), isoparaffinic hydrocarbon compounds, and petroleum fractions (gasoline (C4-C10), naphtha (C4-C11), kerosene / paraffin (C10-C16), and mixtures thereof).

[0166] The lubricant preferably has a water content of 1000 ppm or less. A moisture content of 1000 ppm or less is preferable in terms of reducing deterioration of the electrochemical device, and the moisture content is more preferably 500 ppm or less.

[0167] When the above-mentioned lubricant is used, it is particularly preferable that the lubricant is a low polarity solvent such as heptane or xylene, or an ionic liquid.

[0168] When the above lubricant is used, the amount thereof may be 5.0 to 35.0 parts by weight, preferably 10.0 to 30.0 parts by weight, and more preferably 15.0 to 25.0 parts by weight, based on the total weight of the composition used in step (a1).

[0169] It is preferable that the raw material composition does not substantially contain a liquid medium. In the conventional electrode mixture forming method, a solvent in which a binder is dissolved is used to prepare a slurry in which powders, which are the electrode mixture components, are dispersed, and the electrode mixture sheet is prepared by applying and drying the slurry. In this case, a solvent that dissolves the binder is used. However, the solvents that can dissolve the binder resins that have been commonly used in the past are limited to specific solvents such as butyl butyrate. These react with the solid electrolyte and deteriorate the solid electrolyte, which may cause a decrease in battery performance. In addition, the binder resins that can be dissolved in low-polarity solvents such as heptane are very limited, and the flash point is low, making handling difficult.

[0170] By using a powdered binder with low moisture content without using a solvent when forming the electrode mixture sheet, a battery with less deterioration of the solid electrolyte can be manufactured. Furthermore, in the above-mentioned manufacturing method, an electrode mixture sheet containing a binder having a fine fiber structure can be manufactured, and by not preparing a slurry, the burden of the manufacturing process can be reduced.

[0171] Step (b) is calendering or extrusion. Calendering and extrusion can be performed by a known method. By this, it is possible to form the electrode mixture sheet into a shape. The step (b) preferably includes the steps of (b1) forming the electrode mixture obtained in the step (a) into a bulk form, and (b2) calendaring or extrusion molding the bulk form of the electrode mixture.

[0172] Forming into a bulk form means forming the electrode mixture into a single mass. Specific methods for forming the material into a bulk form include extrusion molding, press molding, and the like. In addition, the term "bulk" does not specify a particular shape, and may refer to a state in which the material is in the form of a single mass, including rods, sheets, spheres, cubes, etc. The size of the mass is preferably such that the diameter or the smallest side of the cross section is 10,000 μm or more, more preferably 20,000 μm or more.

[0173] A specific example of the calendering or extrusion molding method in the above step (b2) is a method in which the electrode mixture is rolled using a roll press machine, a calender roll machine or the like.

[0174] The above step (b) is preferably carried out at 30 to 150° C. As described above, PTFE has a glass transition temperature around 30° C., and therefore is easily fibrillated at temperatures of 30° C. or higher. Therefore, the step (b) is preferably carried out at such a temperature.

[0175] And, calendaring or extrusion applies a shear force, which fibrillates the PTFE and forms it into a shape.

[0176] It is also preferable to have a step (c) after step (b) in which a larger load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also preferable to repeat step (c). In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (c) is preferably from 2 to 10, and more preferably from 3 to 9. A specific rolling method includes, for example, a method in which a rolled sheet is passed between two or more rotating rolls to process it into a thinner sheet.

[0177] From the viewpoint of adjusting the sheet strength, it is also preferable to have a step (d) after the step (b) or the step (c) of crushing the rolled sheet, forming it into a bulk shape again, and rolling it into a sheet shape. It is also preferable to repeat the step (d). The number of times of the step (d) is preferably 1 to 12 times, more preferably 2 to 11 times.

[0178] In step (d), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include folding the rolled sheet, forming it into a rod or thin sheet shape, chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (b) or (c) into another shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.

[0179] Furthermore, step (c) may be carried out after step (d), or may be carried out repeatedly. Moreover, uniaxial or biaxial stretching may be carried out in steps (a), (b), (c) and (d). Furthermore, the sheet strength can also be adjusted by the degree of coarse crushing in step (d).

[0180] In the above steps (b), (c) or (d), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% ​​or less, and even more preferably 50% or less. If the rolling ratio is below the above range, the number of rolling times increases and it takes time, which affects productivity. If the rolling ratio is above the above range, fibrillation may proceed excessively, resulting in an electrode mixture sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after rolling to the thickness before rolling. The sample before rolling may be a bulk raw material composition or a sheet-like raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling. The above steps (c) and (d) are preferably carried out at 30° C. or higher, more preferably 60° C. or higher, and preferably at 150° C. or lower.

[0181] The electrode mixture sheet can be used as an electrode mixture sheet for a secondary battery. It can be used for either a negative electrode or a positive electrode. In particular, the electrode mixture sheet is suitable for a lithium ion secondary battery.

[0182] The present disclosure also provides an electrode comprising the above-mentioned PTFE of the present disclosure or the binder for electrochemical devices of the present disclosure, an electrode active material, and a current collector. The electrode of the present disclosure has excellent strength.

[0183] The electrode of the present disclosure may include the above-mentioned electrode mixture of the present disclosure (preferably an electrode mixture sheet) and a current collector.

[0184] The electrodes of the present disclosure may be positive electrodes or negative electrodes.

[0185] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.

[0186] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0187] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.

[0188] The thickness ratio of the current collector to the positive electrode mixture is not particularly limited, but the value of (thickness of the positive electrode mixture on one side immediately before the electrolyte is injected) / (thickness of the current collector) is preferably 20 or less, more preferably 15 or less, most preferably 10 or less, and is preferably 0.5 or more, more preferably 0.8 or more, most preferably 1 or more. If it exceeds this range, the current collector may generate heat due to Joule heat during high current density charge and discharge. If it is below this range, the volume ratio of the current collector to the positive electrode active material increases, and the battery capacity may decrease.

[0189] The positive electrode may be manufactured by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0190] The density of the positive electrode mixture sheet is preferably 3.00 g / cm 3 More preferably, 3.10 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current density, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0191] The area of ​​the positive electrode mixture sheet is preferably made larger than the outer surface area of ​​the battery exterior case from the viewpoint of increasing the stability at high output and high temperature. Specifically, the total electrode mixture area of ​​the positive electrode relative to the surface area of ​​the exterior of the secondary battery is preferably 15 times or more in area ratio, and more preferably 40 times or more. In the case of a bottomed rectangular shape, the outer surface area of ​​the battery exterior case refers to the total area calculated from the vertical, horizontal and thickness dimensions of the case part filled with the power generating element excluding the protruding part of the terminal. In the case of a bottomed cylindrical shape, it is the geometric surface area of ​​the case part filled with the power generating element excluding the protruding part of the terminal as a cylinder. The total electrode mixture area of ​​the positive electrode is the geometric surface area of ​​the positive electrode mixture layer facing the mixture layer containing the negative electrode active material, and in a structure in which a positive electrode mixture layer is formed on both sides via a collector foil, it refers to the sum of the areas calculated separately for each side.

[0192] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less, on one side of the current collector.

[0193] The positive electrode may have a surface to which a substance of a different composition is attached, such as oxides, such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates, such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates, such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0194] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0195] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0196] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0197] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current density, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0198] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less on one side of the current collector.

[0199] The present disclosure also provides a secondary battery comprising the electrode of the present disclosure described above.

[0200] The secondary battery of the present disclosure may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery.

[0201] The secondary battery using the above-mentioned electrolyte may use electrolytes, separators, etc. that are used in known secondary batteries. These will be described in detail below.

[0202] The electrolyte is preferably a non-aqueous electrolyte, which may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.

[0203] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.

[0204] Examples of the electrolyte salt include LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, and LiN(SO2C2F5)2. From the viewpoint of good cycle characteristics, LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or combinations thereof are particularly preferred.

[0205] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.

[0206] The secondary battery using the above-mentioned electrolyte preferably further includes a separator. The material and shape of the separator are not particularly limited as long as they are stable to the electrolyte and have excellent liquid retention, and any known separator can be used. Among them, it is preferable to use a material formed of a material stable to the electrolyte, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.

[0207] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. These materials may be used alone or in any combination and ratio, such as polypropylene / polyethylene two-layer film and polypropylene / polyethylene / polypropylene three-layer film. Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, because of its excellent electrolyte permeability and shutdown effect.

[0208] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the entire electrolyte battery may be reduced.

[0209] Furthermore, when a porous material such as a porous sheet or nonwoven fabric is used as the separator, the porosity of the separator is optional, but is usually 20% or more, preferably 35% or more, more preferably 45% or more, and is usually 90% or less, preferably 85% or less, more preferably 75% or less. If the porosity is too small, the membrane resistance tends to increase and the rate characteristics tend to deteriorate. If the porosity is too large, the mechanical strength of the separator tends to decrease and the insulating properties tend to decrease.

[0210] The average pore size of the separator is also optional, but is usually 0.5 μm or less, preferably 0.2 μm or less, and usually 0.05 μm or more. If the average pore size exceeds the above range, short circuits are likely to occur. If the average pore size is below the above range, the membrane resistance increases and the rate characteristics may deteriorate.

[0211] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.

[0212] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator can be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of a positive electrode and / or a negative electrode using a resin binder. For example, a porous layer can be formed on both sides of a positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fluororesin as a binder.

[0213] The electrode mixture group may be either a laminated structure of the positive electrode and the negative electrode with the separator interposed therebetween, or a structure of the positive electrode and the negative electrode spirally wound with the separator interposed therebetween. The ratio of the volume of the electrode mixture group to the internal volume of the battery (hereinafter referred to as the electrode mixture group occupancy rate) is usually 40% or more, preferably 50% or more, and usually 90% or less, preferably 80% or less.

[0214] If the electrode mixture group occupancy rate is below the above range, the battery capacity will be small, while if it exceeds the above range, the void space will be small, and the battery will become hot, causing the components to expand and the vapor pressure of the electrolyte liquid component to increase, resulting in an increase in internal pressure, which will degrade various characteristics of the battery, such as repeated charge / discharge performance and high-temperature storage, and may even cause the gas release valve that releases the internal pressure to operate.

[0215] The current collecting structure is not particularly limited, but in order to more effectively improve the charge / discharge characteristics at high current density by the electrolyte, it is preferable to use a structure that reduces the resistance of the wiring and joints. When the internal resistance is reduced in this way, the effect of using the electrolyte is particularly good.

[0216] In the case where the electrode mixture group has the above-mentioned laminated structure, a structure formed by bundling the metal core parts of each electrode mixture layer and welding them to a terminal is preferably used. When the area of ​​one electrode mixture is large, the internal resistance increases, so it is also preferably used to reduce the resistance by providing multiple terminals in the electrode mixture. In the case where the electrode mixture group has the above-mentioned wound structure, the internal resistance can be reduced by providing multiple lead structures on each of the positive electrode and the negative electrode and bundling them to a terminal.

[0217] The material of the exterior case is not particularly limited as long as it is a material stable against the electrolyte used. Specifically, metals such as nickel-plated steel plate, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminate film of resin and aluminum foil (laminate film) are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminate film are preferably used.

[0218] In the case of an exterior case using metals, there are cases in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed structure, or cases in which the metals are used via a resin gasket to form a crimped structure. In the case of an exterior case using the laminate film, there are cases in which the resin layers are heat-sealed together to form a sealed structure. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via a current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.

[0219] The shape of the secondary battery using the above-mentioned electrolyte solution is arbitrary, and examples of the shape include a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the separator can be changed according to the shape of each battery.

[0220] The solid-state secondary battery is preferably an all-solid-state secondary battery. The solid-state secondary battery is preferably a lithium ion battery, and is also preferably a sulfide-based all-solid-state secondary battery. The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode. In the solid secondary battery, the binder of the present disclosure may be used in the electrode layer or in the solid electrolyte layer. A solid secondary battery mix (preferably a mix sheet) containing the binder and solid electrolyte of the present disclosure, and a solid electrolyte layer (preferably a solid electrolyte layer sheet) containing the binder and solid electrolyte of the present disclosure are also suitable aspects of the present disclosure.

[0221] The solid electrolyte used in the solid secondary battery mixture may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, it has the advantage of being flexible.

[0222] The above-mentioned sulfide solid electrolyte is not particularly limited, and examples include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 Si 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4 (x = 0.6 to 0.8), Li 4+y Ge 1-y Ga y S4 (y = 0.2 to 0.3), LiPSCl, LiCl, Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5), etc., or a mixture of two or more thereof can be used.

[0223] The above-mentioned sulfide solid electrolyte preferably contains lithium. The sulfide solid electrolyte containing lithium is used in a solid battery that uses lithium ions as carriers, and is particularly preferable in terms of an electrochemical device having a high energy density.

[0224] The above-mentioned oxide solid electrolyte is preferably a compound that contains an oxygen atom (O), has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electronic insulation.

[0225] Specific compound examples include, for example, Li xa La ya TiO3 [xa = 0.3 to 0.7, ya = 0.3 to 0.7] (LLT), Li xb La yb Zr zb M bb mb Onb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (where 1≦xd≦3, 0≦yd≦2, 0≦zd≦2, 0≦ad≦2, 1≦md≦7, 3≦nd≦15), Li (3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf (1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) N w (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 Examples of such ceramic materials include LLZ (LLZ-based ceramic materials). Ceramic materials in which element substitution has been performed on LLZ are also known. For example, LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) has been performed on LLZ are also known. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON in which part of the oxygen in lithium phosphate has been replaced with nitrogen, LiPOD, etc. 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.

[0226] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0227] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. Oxides having a crystalline structure are particularly preferred in terms of good Li-ion conductivity. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet type (Li7La3Zr2O 12 (LLZ), etc. Among these, the NASICON type is preferred.

[0228] The volume average particle diameter of the oxide-based solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, and more preferably 0.03 μm or more. The upper limit is preferably 100 μm or less, and more preferably 50 μm or less. The average particle diameter of the oxide-based solid electrolyte particles is measured by the following procedure. The oxide-based solid electrolyte particles are diluted and adjusted to a 1 mass% dispersion in a 20 ml sample bottle using water (heptane in the case of a substance unstable in water). The diluted dispersion sample is irradiated with 1 kHz ultrasonic waves for 10 minutes and used for testing immediately thereafter. Using this dispersion sample, data is taken 50 times using a laser diffraction / scattering type particle size distribution measuring device LA-920 (manufactured by HORIBA) at a temperature of 25°C using a measurement quartz cell to obtain the volume average particle diameter. For other detailed conditions, etc., refer to the description of JISZ8828:2013 "Particle size analysis - dynamic light scattering method" as necessary. Five samples are prepared for each level and the average value is adopted.

[0229] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0230] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0231] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.

[0232] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0233] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.

[0234] Various physical properties were measured by the following methods.

[0235] Average primary particle size The PTFE aqueous dispersion was diluted with water until the solid content concentration was 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph were measured to create a calibration curve. Using this calibration curve, the number-average particle diameter was determined from the measured transmittance of the 550 nm projected light of each sample, and was taken as the average primary particle diameter.

[0236] Polymer Solids Content 1 g of the aqueous PTFE dispersion was dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass (1 g) of the aqueous dispersion was expressed as a percentage and used.

[0237] Aspect Ratio A PTFE aqueous dispersion diluted to a solids concentration of approximately 1% by mass was observed with a scanning electron microscope (SEM), and images of more than 200 randomly selected particles were processed to determine the average ratio of their major axis to their minor axis.

[0238] VDF content PTFE powder 19 F-NMR was measured. In addition, a thin film disk was produced by pressing the PTFE powder, and the infrared absorbance measured by FT-IR was 1429 cm -1 / 2360cm -1 The absorbance ratio was calculated. A calibration curve was created from the above absorbance ratio. The VDF content was calculated from this calibration curve.

[0239] HFP content PTFE powder 19 The F-NMR measurement was performed, and the signal derived from the functional group was calculated based on the following formula. HFP content (mass%)=(50A / (50A+25B))×100 (A: integral value of the CF3 signal appearing around -65 ppm, B: integral value of the CF2 signal appearing around -120 ppm) The chemical shift value was determined by setting the peak top of the CF2 signal derived from the polymer main chain at −120 ppm.

[0240] CTFE content A thin film disk was made by pressing PTFE powder, and the infrared absorbance of the thin film disk was measured by FT-IR. -1 Absorbance / 2360cm -1 The absorbance ratio was multiplied by 0.58.

[0241] PMVE content The PTFE powder is melted at 370℃. 19 F-NMR measurement was performed, and the values ​​were calculated based on the following formula from the signals derived from the functional groups obtained. PMVE content (mass%)=(664B / (300A+364B))×100 (A: Total integral of the CF2 signal appearing around -120 ppm and the CF signal appearing around -136 ppm, B: Integrated value of the PMVE-derived CF3 signal appearing around -54 ppm) The chemical shift value was determined by setting the peak top of the CF2 signal derived from the polymer main chain at −120 ppm.

[0242] Standard specific gravity (SSG) The measurements were made using samples formed in accordance with ASTM D 4895 and by the water displacement method in accordance with ASTM D 792.

[0243] Endothermic peak temperature The endothermic peak temperature was determined as the temperature corresponding to the minimum point on the heat of fusion curve when PTFE that had not been heated to a temperature of 300°C or higher was heated at a rate of 10°C / min using a differential scanning calorimeter (DSC).

[0244] Number average molecular weight (Mn) The heat of crystallization was estimated by measuring the temperature drop of a differential scanning calorimeter (DSC) after melting PTFE, and was calculated according to the method described in the following document. The measurement was carried out five times, and the average value of the three values ​​excluding the maximum and minimum values ​​was used. Literature: Suwa, T.; Takehisa, M.; Machi, S., J. Appl. Polym. Sci. vol. 17, pp. 3253 (1973).

[0245] moisture content Approximately 20 g of PTFE powder was heated at 150°C for 2 hours, the mass was measured before and after, and the mass was calculated according to the following formula. A sample was taken three times, and the mass was calculated for each time, and the average value was calculated. Moisture content (mass%) = [(mass (g) of PTFE powder before heating) - (mass (g) of PTFE powder after heating)] / (mass (g) of PTFE powder before heating) x 100

[0246] Average secondary particle size Measurements were performed in accordance with JIS K6891.

[0247] apparent density Measurements were performed in accordance with JIS K6892.

[0248] RR100 extrusion pressure (extrusion pressure at reduction ratio 100) 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name: Isopar E, ExxonMobil) as an extrusion aid were mixed in a polyethylene container for 3 minutes. At room temperature (25±2°C), the above mixture was filled into the cylinder of an extruder, and a load of 0.47 MPa was applied to the piston inserted into the cylinder and held for 1 minute. The mixture was then extruded from the orifice at a ram speed of 18 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice was 100. In the latter half of the extrusion operation, the load (N) when the pressure reached equilibrium was divided by the cross-sectional area of ​​the cylinder to obtain the extrusion pressure (MPa).

[0249] Extension test The bead obtained by the above paste extrusion was dried at 230°C for 30 minutes to remove the lubricant. The dried bead was cut to an appropriate length and placed in an oven heated to 300°C. In the oven, it was stretched at a stretching speed of 100% / sec until it reached 25 times its length before the stretching test. Those that did not break during stretching were evaluated as being stretchable at a stretching speed of 100% / sec.

[0250] Fluorine-containing compound content 1 g of PTFE powder was weighed out, 10 g (12.6 ml) of methanol was added, and ultrasonic treatment was performed for 60 minutes to obtain an extract. The obtained extract was measured by LC / MS / MS. The fluorine-containing compounds in the extract were measured using a liquid chromatograph mass spectrometer (Waters, LC-MS ACQUITY UPLC / TQD). The measurement equipment configuration and LC-MS measurement conditions are shown in Table 1. Using an aqueous solution of a fluorine-containing compound with a known concentration, aqueous solutions with five or more levels of content were prepared, and LC / MS analysis was performed for each content. The relationship between the content and the area area relative to the content was plotted to draw a calibration curve. Using the above calibration curve, the area area of ​​the LC / MS chromatogram of the fluorine-containing compound in the extract was converted to the content of the fluorine-containing compound. The lower detection limit in this measurement method is 10 ppb by mass.

[0251] [Table 1]

[0252] Synthesis Example 1 A white solid A was obtained by the method described in Synthesis Example 1 of WO 2021 / 045228.

[0253] Preparation example 1 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After injecting 0.50 g of HFP with TFE, TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 70 ° C. while stirring. Next, an aqueous solution of 15.4 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 430 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached 1540 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The solid content concentration of the obtained aqueous PTFE dispersion was 29.6 mass%, and the average primary particle size was 246 nm.

[0254] Example 1 The PTFE aqueous dispersion obtained in Preparation Example 1 was diluted to a solid concentration of 13% by mass, stirred in a container equipped with a stirrer to solidify, and then filtered from the water to obtain a wet powder. The obtained wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulating electric furnace at 180°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. The physical properties of the obtained PTFE powder were measured, and the results are shown in Table 2.

[0255] Example 2 Except for changing the amount of HFP charged to 0.06 g, an aqueous PTFE dispersion was obtained in the same manner as in Preparation Example 1. The solid content concentration of the obtained aqueous PTFE dispersion was 29.2 mass %, and the average primary particle size was 274 nm.

[0256] Example 2 The PTFE aqueous dispersion obtained in Preparation Example 2 was used to obtain a PTFE powder in the same manner as in Example 1, except that the heat treatment temperature was changed to 160°C. The physical properties of the obtained PTFE powder were measured, and the results are shown in Table 2.

[0257] Preparation example 3 In a 6L stainless steel reactor equipped with a stirrer, 3600g of deionized water, 180g of paraffin wax, and 5.4g of white solid A were placed. The reactor contents were then heated to 80°C while being aspirated, and purged with tetrafluoroethylene (TFE) to remove oxygen from the reactor, and the contents were stirred. 3.1g of vinylidene fluoride (VDF) was pressurized into the reactor with TFE, and TFE was then added to bring the pressure to 2.70MPaG. An aqueous solution of 7.2mg of ammonium persulfate (APS) dissolved in deionized water as an initiator was added to the reactor. After the initiator was injected, a pressure drop occurred and the start of polymerization was observed. TFE was added to the reactor to keep the pressure constant at 2.70MPaG. When the amount of TFE charged reached 430g, an aqueous solution of 18.2mg of hydroquinone dissolved in deionized water was added. When the amount of TFE charged reached 1580 g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was evacuated until it reached normal pressure, and nitrogen replacement was performed, and the contents were removed from the reactor and cooled. The paraffin wax was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 30.3 mass%, and the average primary particle size was 223 nm.

[0258] Example 3 The PTFE aqueous dispersion obtained in Preparation Example 3 was diluted to a solid content concentration of 13% by mass, vigorously stirred in a container equipped with a stirrer to solidify, and then filtered from the water to obtain a wet powder. The obtained wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 2.

[0259] Preparation Example 4 In a 6L stainless steel reactor equipped with a stirrer, 3600g of deionized water, 180g of paraffin wax, 5.4g of white solid A, and 0.0265g of oxalic acid were placed. The contents of the reactor were then heated to 70°C while being aspirated, and purged with tetrafluoroethylene (TFE) to remove oxygen from the reactor, and the contents were stirred. 1.70g of vinylidene fluoride (VDF) was pressurized into the reactor with TFE, and TFE was then added to make the pressure 2.70MPaG. An aqueous solution of potassium permanganate, in which 3.4mg of potassium permanganate was dissolved in deionized water, was continuously added to the reactor as an initiator. After the injection of the initiator, a drop in pressure occurred and the start of polymerization was observed. TFE was added to the reactor to keep the pressure constant at 2.70MPaG. When the amount of TFE charged reached 430g, the charging of the aqueous potassium permanganate solution was stopped. When the amount of TFE charged reached 1815 g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was evacuated until it reached normal pressure, and nitrogen replacement was performed, and the contents were removed from the reactor and cooled. The paraffin wax was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 33.3 mass%, and the average primary particle size was 251 nm.

[0260] Example 4 The PTFE aqueous dispersion obtained in Preparation Example 4 was diluted to a solid content concentration of 13% by mass, vigorously stirred in a container equipped with a stirrer to solidify, and then filtered from the water to obtain a wet powder. The obtained wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 2.

[0261] Preparation example 5 In a 6L SUS reactor equipped with a stirrer, 3480g of deionized water, 100g of paraffin wax, and 5.25g of white solid A were placed. The contents of the reactor were then heated to 70°C while being aspirated, and purged with tetrafluoroethylene (TFE) at the same time to remove oxygen from the reactor, and the contents were stirred. TFE was injected into the reactor to set the system pressure to 0.78MPaG, and the system temperature was maintained at 70°C while stirring. Next, an aqueous solution of 15.0mg of ammonium persulfate dissolved in 20g of water was injected with TFE to initiate the polymerization reaction. As the polymerization reaction proceeded, the system pressure decreased, but TFE was added to maintain the system temperature at 70°C and the system pressure at 0.78MPaG. When 400 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerization reached 1200 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The solid content concentration of the obtained aqueous PTFE dispersion was 25.3 mass%, and the average primary particle size was 310 nm.

[0262] Comparative Example 1 The PTFE aqueous dispersion obtained in Preparation Example 5 was diluted to a solids concentration of 13 mass %, and the PTFE was solidified while being vigorously stirred in a vessel equipped with a stirrer, and then the water was separated by filtration to obtain a wet powder. The obtained PTFE wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulating electric furnace at 210° C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.159, and the number average molecular weight was 2.1 × 10 6 It was.

[0263] <Preparation of positive electrode mixture sheet> Li(Ni 0.6 Mn 0.2 Co 0.2)O2[NMC622] and PTFE powder as a binder were weighed out and cooled thoroughly in a refrigerator to bring the materials to 5°C. The cooled NMC622 and binder were put into a high-speed stirring mixer and the materials were dispersed (1 min, 3000 rpm). Then, carbon black [SUPER P-Li] was weighed as a conductive additive, and the mixture was stirred at 30 rpm for 300 seconds using a pressure kneader heated to 40°C to obtain a mixture. The composition was adjusted to a mass ratio of positive electrode active material: binder: conductive additive = 96:2:2. The mixture obtained is placed in a rolling mill heated to 80°C and rolled to a thickness of 1 to 2 cm. 2 These chips were again fed into the rolling rolls heated to 80° C. several times to obtain sheets. Then, the thickness and density are adjusted using a roll press machine to a thickness of about 90 μm and a density of 3.6 g / cm 3 Thus, a positive electrode mixture sheet was obtained.

[0264] <Electrode strength measurement> The positive electrode mixture sheet was cut out to prepare a rectangular test piece having a width of 4 mm. A tensile tester (AGS-100NX manufactured by Shimadzu Corporation) was used to measure at 100 mm / min. The distance between the chucks was 30 mm. Displacement was applied until breakage, and the maximum stress of the measurement results was taken as the strength of each sample. Comparative Example 1 was set to 100 for comparison.

[0265] The PTFE powders obtained above were used to prepare positive electrode mixture sheets by the method described above, and the results were evaluated. The results are shown in Table 2.

[0266] [Table 2]

[0267] Preparation Example 6 In a 6L stainless steel reactor equipped with a stirrer, 3600g of deionized water, 180g of paraffin wax, 5.4g of white solid A, and 26.5mg of oxalic acid were placed. The contents of the reactor were then heated to 70°C while being aspirated, and purged with tetrafluoroethylene (TFE) to remove oxygen from the reactor, and the contents were stirred. 2.7g of chlorotrifluoroethylene (CTFE) was pressed into the reactor with TFE, and TFE was then added to make the pressure 2.70MPaG. An aqueous solution of potassium permanganate, in which 3.5mg of potassium permanganate was dissolved in deionized water, was continuously added to the reactor as an initiator. After the injection of the initiator, a pressure drop occurred and the start of polymerization was observed. TFE was added to the reactor to keep the pressure constant at 2.70MPaG. When the amount of TFE charged reached 430g, the charging of the aqueous potassium permanganate solution was stopped. When the amount of TFE charged reached 1660 g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was evacuated until it reached normal pressure, and nitrogen replacement was performed, and the contents were removed from the reactor and cooled. The paraffin wax was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 31.4 mass%, and the average primary particle size was 245 nm.

[0268] Example 5 The PTFE aqueous dispersion obtained in Preparation Example 6 was diluted to a solid content concentration of 13% by mass, vigorously stirred in a container equipped with a stirrer to solidify, and then filtered from the water to obtain a wet powder. The obtained wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 3.

[0269] Preparation Example 7 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3560 g of deionized water, 100 g of paraffin wax, and 5.4 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to set the system pressure to 0.60 MPaG, and the system temperature was maintained at 70 ° C. while stirring. Next, 0.30 g of perfluoro(methyl vinyl ether) (PMVE) was injected with TFE. Next, an aqueous solution in which 15.0 mg of ammonium persulfate was dissolved in 20 g of water was injected with TFE, the system pressure was set to 0.78 MPaG, and the polymerization reaction was started. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 429 g of TFE was consumed from the start of polymerization, an aqueous solution of 14.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerization reached 1225 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The solid content concentration of the obtained aqueous PTFE dispersion was 25.4 mass%, and the average primary particle size was 246 nm.

[0270] Example 6 The PTFE aqueous dispersion obtained in Preparation Example 7 was diluted to a solid content concentration of 13% by mass, vigorously stirred in a container equipped with a stirrer to solidify, and then filtered from the water to obtain a wet powder. The obtained wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 3.

[0271] [Table 3]

Claims

1. Polytetrafluoroethylene used in a binder for electrochemical devices, having a number average molecular weight of 3.0×10 6 Polytetrafluoroethylene having a water content of 0.050 mass% or less.

2. A binder for electrochemical devices consisting essentially of polytetrafluoroethylene, wherein the polytetrafluoroethylene has a number average molecular weight of 3.0×10 6 The binder for electrochemical devices is as described above.

3. 3. The binder for electrochemical devices according to claim 2, wherein the polytetrafluoroethylene has a moisture content of 0.050% by mass or less.

4. 4. The binder for electrochemical devices according to claim 2, wherein the average aspect ratio of primary particles of the polytetrafluoroethylene is 2.0 or less.

5. 4. The binder for electrochemical devices according to claim 2, wherein the polytetrafluoroethylene has an extrusion pressure of 50 MPa or less at a reduction ratio of 100.

6. 4. The binder for electrochemical devices according to claim 2, wherein the polytetrafluoroethylene is stretchable.

7. 4. The binder for electrochemical devices according to claim 2 or 3, which is a binder for batteries.

8. 4. An electrode mixture comprising the polytetrafluoroethylene according to claim 1 or the binder for electrochemical devices according to claim 2 or 3, and an electrode active material.

9. The electrode mixture according to claim 8, which is in the form of a sheet.

10. 4. An electrode comprising the polytetrafluoroethylene according to claim 1 or the binder for electrochemical devices according to claim 2 or 3, an electrode active material, and a current collector.

11. A secondary battery comprising the electrode according to claim 10.

Citation Information

Patent Citations

  • Dispersion containing tetrafluoroethylene copolymer particle and its production

    JP1999343317A

  • Polytetrafluoroethylene powder, electrode material, electrode and fuel cell

    JP2003342436A

  • Binder for electrode material

    JP2004031179A

  • Electrode having polytetrafluoroethylene-containing binder layer

    JP2015038818A

  • Dry electrode for energy storage device and its manufacturing method

    JP2017517862A